2010
DOI: 10.1007/s11060-010-0454-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis by unenhanced FLAIR T2-weighted magnetic resonance images between solitary high grade gliomas and cerebral metastases appearing as contrast-enhancing cortico-subcortical lesions

Abstract: The aim was to assess the value of unenhanced fluid-attenuated inversion recovery T2-weighted sequences (FLAIR-T2) in the differential diagnosis between solitary high-grade gliomas (HGG) and cerebral metastases (CM) appearing as contrast-enhancing cortico-subcortical lesions of the brain. In 69 patients with a contrast-enhancing cortico-subcortical brain lesion (43 HGG, and 26 CM), unenhanced FLAIR-T2 and gadolinium-enhanced FLAIR T1-weighted (Gd-FLAIR-T1) axial images have been reviewed for the involvement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…The occurrence of nCS in around half of our patients with glioblastoma is consistent with prior studies, but in a much larger cohort, reaffirming that the finding is a common feature of glioblastomas. While others have suggested that nCS may be an imaging biomarker of secondary glioblastomas, our results do not support this.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The occurrence of nCS in around half of our patients with glioblastoma is consistent with prior studies, but in a much larger cohort, reaffirming that the finding is a common feature of glioblastomas. While others have suggested that nCS may be an imaging biomarker of secondary glioblastomas, our results do not support this.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of non‐enhancing cortical signal abnormality (nCS) on T2‐weighted fluid‐attenuated inversion recovery (FLAIR) sequences contiguous with an enhancing glioblastoma has been shown to be a useful feature for differentiating it from other diagnoses, in particular metastatic disease . In the two larger studies, both of which assessed solitary enhancing lesions, nCS occurred in 63% and 44% of patients, respectively . To our knowledge, the prognostic implications of nCS have not been previously assessed, although other authors have studied the prognostic significance of non‐contrast‐enhancing tumour (nCET) in general, and there is growing interest in this topic.…”
Section: Introductionmentioning
confidence: 99%
“…In a solitary enhancing cerebral lesion, the presence of non-enhancing involvement of the adjacent cortex, with signal intensity abnormality on FLAIR or T2-weighted imaging, is a frequent and relatively specific sign for glioblastoma (62,63).…”
Section: Advanced Mr Imagingmentioning
confidence: 99%
“…MRI may then provide a specific diagnosis from this limited differential, for example by demonstrating the extra-axial location and dural tail of a meningioma (Fig. 4), cortical FLAIR hyperintensity in a glioma [2, 3], the characteristic cystic mass with a contrast-enhancing mural nodule in the case of a haemangioblastoma [10], the presence of additional lesions in a patient with metastatic disease (Fig. 5), or the olfactory groove epicentre of an esthesioneuroblastoma.…”
Section: How We Read Mri and Pet Together In Neuro-oncologymentioning
confidence: 99%
“…Volumetric pre- and post-contrast T1-weighted imaging are important, as one of the key advantages of MRI over PET is the improved anatomical delineation that fine-slice imaging provides. As standard, we also suggest axial T2-weighted imaging, FLAIR (Fluid Attenuated Inversion Recovery), DWI (diffusion-weighted imaging) and a susceptibility-sensitive sequence such as SWI (Susceptibility-Weighted Imaging), as these can provide a confident diagnosis of pathologies such as a glioma [2, 3] or pyogenic abscess [4, 5]. Perfusion-weighted imaging and spectroscopy may be added depending on the differential diagnosis based on PET.…”
Section: Introductionmentioning
confidence: 99%